Studying gender in the neoliberal, postfeminist university: Australian university students' perspectives. (June 2021) - La Paglia, Heidi; Nash, Meredith; Grant, Ruby
In a neoliberal environment where university students are encouraged to study subjects and courses which will lead to specific job outcomes, this article explores which students undertake Women's and Gender Studies (WGS), why they undertake the degree, and what it teaches them. Drawing on interviews with students at a regional Australian university, this qualitative study examines the extent to which the university's Gender Studies cohort is postfeminist, and the impact that this has on retention and student outcomes. Findings suggest that WGS holds an ambivalent position within the contemporary university context. While students claim that studying WGS may not directly benefit them in the contemporary job market, they choose to study it because it gives them a better understanding of themselves and the world around them. The value students place on WGS is an insight rarely recognised previously.